Genetic affinities of Jewish populations. - Livshits, G (1991)
Genetic relations between various Jewish (J) and non-Jewish (NJ) populations were assessed using two sets of data. The first set contained 12 pairs of matched J and NJ populations from Europe, the Middle East, and North Africa, for which 10 common polymorphic genetic systems (13 loci) were available. The second set included 22 polymorphic genetic systems (26 loci) with various numbers of populations (ranging from 21 to 51) for each system. Therefore, each system was studied separately. Nei's standard genetic distance (D) matrices obtained for these two sets of data were tested against design matrices specifying hypotheses concerning the affiliations of the tested populations. The tests against single designs were carried out by means of Mantel tests. Our results consistently show lower distances among J populations than with their NJ neighbors, most simply explained by the common origin of the former. Yet, there is evidence also of genetic similarity between J and corresponding NJ populations, suggesting reciprocal gene flow between these populations or convergent selection in a common environment. The results of our study also indicate that stochastic factors are likely to have played a role in masking the descent relationships of the J populations.